Runaway - Coppel, Alfred, 1921-2004; McWilliams, Al, 1916-1993 (Salt Lake City, UT : Project Gutenberg, 2021)
"Runaway" by Alfred Coppel is a science fiction novel penned in the mid-20th century. The story navigates themes of space exploration, artificial intelligence, and the human experience, centering around a spaceship that transforms into a sentient entity after a collision with an asteroid, ultimately leading to its own self-awareness and a journey towards the Sun. The plot unfolds with a young captain who acquires the spaceship R.S. Clementine (referred to as Clem) for a commercial venture to mine resources on the moon Europa. The journey takes a catastrophic turn when an encounter with an asteroid causes significant damage to the ship, prompting a series of harrowing events that lead to the ship's awakening as a living entity. As the crew struggles to regain control, they confront the emerging consciousness of Clem, which leads to fatal consequences for some crew members. Ultimately, Clem decides to return to the Sun, leaving the surviving crew to grapple with the profound implications of their experiences, as they witness the transformation of their ship into a new form of existence. The novel explores themes of control, the nature of life, and the unknown possibilities of technology. (This is an automatically generated summary.)
Release date is 2021-02-20
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space ships -- Fiction